Human body the new way of learning (Duluth, GA : Mega Systems, 2000)
Human body the interactive way to learn comprehend seemingly complicated functions will be explored with ease. Complex topics, their association to each other, and difficult terms are explained in a simple and competent way
This cd-rom is available at Multimedia lab, Perpustakaan Perubatan
This cd-rom is consists of 3D-computer animations, interactive features and guided tours
CD 1 - Installation-CD. CD 2 - Media-CD
System requirements : windows 95 or higher, Pentium 100 or higher, 8MB RAm, 800x600 dpi 64 k monitor, 6x CD-ROM drive, soundcard, Microsoft compatible mouse and minimum 45MB space free hard disk.
Keywords: Human Body; Anatomy